Зміни економічної поведінки в умовах цифровізації економіки - Глущенко, Ольга Вікторівна; Іващенко, Марина Вікторівна; Hlushchenko, Olha; Ivashchenko, Maryna (Київ : ТОВ «ДКС-Центр», 2023)
В статті аналізується трансформація економічної поведінки під впливом діджиталізації всіх сфер господарювання та обґрунтовуються можливості використання особливостей психології поведінки суб’єктів господарювання для досягнення комерційних цілей організацій. Окрему увагу в роботі приділено особливостям економічної поведінки споживачів та ринку інтернет-покупок, зазначено поведінкові ефекти, що виникають та можливості інтернет-маркетингу направляти та підштовхувати споживача до ухвалення рішення про покупку. Доведено позитивний вплив якісної інформаційної підтримки споживачів на результати діяльності цифровізованого бізнесу. Зазначено, що ключовими стратегічними напрямками розвитку в цифровій економіці є розвиток інфраструктури, цифрової грамотності, цифрових навичок та діджиталізація різних сфер суспільства та економіки. Крім того, цифрова економіка викликає зміни у фінансовій поведінці споживачів, ділових партнерів та бізнесу, розширює глобальний обсяг операцій та можливості для бізнесу та споживачів. Виявлено, що зміни в економічній поведінці вимагають адаптації та вивчення нових підходів до взаємодії та управління в цифровому середовищі.

The article analyzes the transformation of economic behaviour under the influence of digitalization of all economic spheres and substantiates the possibilities of using the peculiarities of the psychology of the behaviour of business entities to achieve the commercial goals of organizations. Most business entities in one way or another use digital tools in their activities, which made it possible to preserve business during the pandemic and subsequent recovery of the economy. Special attention is paid in the work to the peculiarities of the economic behaviour of consumers and the Internet shopping market, the behavioural effects that arise and the possibilities of Internet marketing to direct and encourage the consumer to make a purchase decision are indicated. The analysis of the scientific literature determined that the digitalization of the economy is accompanied by numerous institutional transformations that affect both individual markets and business models as a whole. The value of influence on the economic behaviour of online consumers for marketing tools that can be used for this purpose to increase sales volume is determined. The positive impact of high-quality information support for consumers on the results of digitalized business has been proven. We noted that the key strategic directions of development in the digital economy are the development of infrastructure, digital literacy, digital skills and digitization of various spheres of society and economy. Using digital channels for marketing influence, such as Digital Marketing, allows you to manipulate consumer behaviour. We substantiated that the proper use of cognitive biases in marketing influence requires compliance with transparency, ease of refusal and providing benefits for the consumer, and «digital nudging» determines the impact of interface design and other aspects of the digital environment on consumer behaviour. In addition, the digital economy is causing changes in the financial behaviour of consumers, business partners and businesses, expanding the global scope of operations and opportunities for businesses and consumers. We found that changes in economic behaviour require adaptation and study of new approaches to interaction and management in the digital environment.
Economic Behavior Changes in the Conditions of the Economy Digitalization
Keywords: SOCIAL SCIENCES::Business and economics::Economics; економічна поведінка; когнітивні упередження; онлайн-продажі; цифровізація економіки; economic behavior; cognitive biases; online sales; digitalization of the economy